Maternidad/maternalidad y trabajo: "efecfos" del rol dual sobre los hijos y la pareja - Ragúz, María (1989)
An overview of sex role literature and recent research on working mothers is presented. Attention focuses on correlational and causal findings concerning the "effects" mothers' dual work has on ther children and husband. The "effects" of work on the mothers themselves are to be dealt with in another article.